Impact of aspirin on biochemical recurrence of prostate cancer after robot assisted radical prostatectomy in a multicenter retrospective cohort study - Shuhei Suzuki; Hiromitsu Negoro; Masashi Kubota; Takayuki Sumiyoshi; Ryoichi Saito; Tomoya Okuno; Takehiko Segawa; Shigeki Fukuzawa; Hiroyuki Onishi; Kodai Hattahara; Kanji Nagahama; Yuya Sekine; et al. (Scientific Reports)
Abstract This study evaluated the impact of aspirin on the biochemical recurrence (BCR) rate following robot-assisted radical prostatectomy (RARP) in patients. A database search identified patients who underwent RARP for pT2-3N0M0 disease at any of 25 centers between 2011 and 2022, categorized into aspirin (n = 350) and control groups (n = 5857). Adjustment by 1:1 propensity score matching (PSM) and Mahalanobis distance matching (MDM) created 350 matched pairs. The effect of aspirin on the BCR rate was evaluated by analysis of BCR-free survival. After PSM and MDM, the 3-year BCR-free rate was significantly better in the aspirin group (85.0%, 95% confidence interval [CI] 80.8–89.4) than in the control group (PSM, 74.5%, 95% CI 66.5–83.5, p = 0.021; MDM, 74.7%, 95% CI 66.3–84.3, p = 0.037). In the analysis of high-risk subgroups, patients in the aspirin group with an ISUP (International Society of Urological Pathology) grade ≥ 4 had a significantly lower recurrence rate in both matched groups (PSM, hazard ratio 0.44, 95% CI 0.22–0.88; MDM, hazard ratio 0.45, 95% CI 0.23–0.90). In conclusion, this study suggests that aspirin could enhance BCR-free survival post-RARP, especially in patients with higher ISUP grades.